MANAGEMENT OF MARGINAL ULCERS IN OBESE PATIENTS AFTER LAPAROSCOPIC GASTRIC BYPASS - Olexander Ioffe; Victor Nevmerzhytskyi (Acta Medica Leopoliensia)
Marginal ulcer (MU) is a frequent late complication in patients after laparoscopic gastric bypass, occurring in 3-25% of patients. During the past 10 years, there has been a decrease in the rate of marginal ulcers, due to the improvement of surgical techniques and the widespread use of proton pump inhibitors II generation. According to the time of occurrence, marginal ulcers are classified into early (up to 30 days after surgery) and late (after 30 days).